Crisis management : global practices for business - Gonen, Ibrahim (United Kingdom : Sharp&Sharp Publishing, 2019)
In this book, strategies that can be applied on a macro and micro basis against critical events of periodic nature are described. The strategies that should be applied in pre-crisis, crisis and post-crisis periods in order to increase the competitiveness of enterprises against periodic events and to enable them to cope with crises by bringing a flexible and strong structure are explained on the sectoral basis.
Chapter 1. Economic Impacts of Global Alterations -- Chapter 2. Significant Critical Periods having the effect on the countries -- Chapter 3. Managing Crisis -- Chapter 4. Scientific Practice to cope the crises -- Chapter 5. Contemporary Management Approaches Against crises -- Chapter 6. Some Key Precautions for the Crises -- Chapter 7. Precautions for the businesses in Crisis Management.
Includes index.
Keywords: CRISIS MANAGEMENT